2018
DOI: 10.2319/112017-801.1
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride reduces orthodontically induced root resorption and affects tooth root movement in rats

Abstract: In rats, LiCl reduced OIRR, which induced mesial movement of the tooth root apex. OIRR positively correlated to cortical bone morphometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…As the concentration of lithium increases, root resorption and tooth movement decrease in animal experiments [38]. As described above, most of the substances administered to reduce root resorption through a mechanism that reduces osteoclast activity have tended to decrease tooth movement speed as well as root resorption [38]. The 4HR used in this study resulted in root resorption being reduced compared to that in the control group (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As the concentration of lithium increases, root resorption and tooth movement decrease in animal experiments [38]. As described above, most of the substances administered to reduce root resorption through a mechanism that reduces osteoclast activity have tended to decrease tooth movement speed as well as root resorption [38]. The 4HR used in this study resulted in root resorption being reduced compared to that in the control group (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 59%
“…Lithium promotes reduced osteoclast formation by promoting the Wnt/β-catenin signaling system [37]. As the concentration of lithium increases, root resorption and tooth movement decrease in animal experiments [38]. As described above, most of the substances administered to reduce root resorption through a mechanism that reduces osteoclast activity have tended to decrease tooth movement speed as well as root resorption [38].…”
Section: Discussionmentioning
confidence: 99%
“…In support of these findings, previous investigations have demonstrated potential benefits of lithium chloride on fracture healing (26,27) and alveolar bone repair (16)(17)(18)(19)(20)(21). Han et al (16) demonstrated that local administration of lithium chloride stimulated greater alveolar bone volume and mineral density during the healing of surgicallycreated periodontal defects in estrogen-sufficient rats.…”
Section: Discussionmentioning
confidence: 76%
“…Pre-clinical dental studies have shown benefits of lithium chloride, in states of both estrogen sufficiency and deficiency, on bone formation during orthodontic retention, midpalatal expansion and surgically-created periodontal defects, for improving implant osseointegration and for the attenuation of bone loss in a model of induced periodontitis (15)(16)(17)(18)(19)(20). A single previous study in estrogen-sufficient rats evaluated the effects of lithium chloride on the healing process of tooth sockets.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, micro CT imaging has been used to investigate root resorption during orthodontic tooth movement for in vivo 1619 and ex vivo studies 2022 . For such applications, one of the advantages of using such a method is that the structure of the tooth root can be mapped down to the micrometer level in three dimensions.…”
Section: Introductionmentioning
confidence: 99%